Sport and social media research: A review - Filo, K.; Lock, D.; Karg, A. (Sport Management Review, 2015)
The emergence of social media has profoundly impacted the delivery and consumption of sport. In the current review we analysed the existing body of knowledge of social media in the field of sport management from a service-dominant logic perspective, with an emphasis on relationship marketing. We reviewed 70 journal articles published in English-language sport management journals, which investigated new media technologies facilitating interactivity and co-creation that allow for the development and sharing of user-generated content among and between brands and individuals (i.e., social media). Three categories of social media research were identified: strategic, operational, and user-focussed. The findings of the review demonstrate that social media research in sport management aligns with service-dominant logic and illustrates the role of social media in cultivating relationships among and between brands and individuals. Interaction and engagement play a crucial role in cultivating these relationships. Discussion of each category, opportunities for future research as well as suggestions for theoretical approaches, research design and context are advanced.